Experimental Estimation of Critical Buckling Velocities for Conservative Pipes Conveying Fluid - Jweeg, Mohsen J.; Ismail, Mahmud R.; Yousif, Albert E. (Al-Khwarizmi Engineering Journal, 2018)
Conservative pipes conveying fluid such as pinned-pinned (p-p), clamped–pinned (c-p) pipes and clamped-clamped (c-c) lose their stability by buckling at certain critical fluid velocities. In order to experimentally evaluate these velocities, high flow-rate pumps that demand complicated fluid circuits must be used. This paper studies a new experimental approach based on estimating the critical velocities from the measurement of several fundamental natural frequencies .In this approach low flow-rate pumps and simple fluid circuit can be used. Experiments were carried out on two pipe models at three different boundary conditions. The results showed that the present approach is more accurate for estimating the critical velocities of p-p and c-p pipes. However, for c-c pipes it was not so unless a higher flow rate is used.